2022
DOI: 10.1155/2022/4658709
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Study of Mobile Application- (App-) Based Family-Centered Care (FCC) Model Combined with Comprehensive Iron Removal Treatment in Children with Severe Beta Thalassemia

Abstract: Background and Objective. Hemoglobinopathy is one of the most prevalent monogenic disorders in the world. Thalassemia is characterized by autosomal recessive deficiencies in hemoglobin production. The difficulties of iron overload caused by transfusions, which are the foundation of illness management in the majority of patients with severe thalassemia, may further worsen the clinical features. There are numerous obstacles and restrictions to the currently accessible conventional therapy for thalassemia. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This has been proven to improve the management of thalassemia patients (Banjar et al, 2021). The application used can also be applied to families or caregivers of thalassemia patients using the mobile application-based Family Central Care (FCC) implementation model which can significantly improve family functions in helping thalassemia patients improve quality of life, self-care ability, medication adherence and application value high clinical (Chen et al, 2022). Family or caregivers play an important role in meeting the needs of thalassemia patients who also need to obtain detailed and dynamic information regarding thalassemia disease suffered by their family members.…”
Section: Discussionmentioning
confidence: 99%
“…This has been proven to improve the management of thalassemia patients (Banjar et al, 2021). The application used can also be applied to families or caregivers of thalassemia patients using the mobile application-based Family Central Care (FCC) implementation model which can significantly improve family functions in helping thalassemia patients improve quality of life, self-care ability, medication adherence and application value high clinical (Chen et al, 2022). Family or caregivers play an important role in meeting the needs of thalassemia patients who also need to obtain detailed and dynamic information regarding thalassemia disease suffered by their family members.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%